(3Jbhje GdUMI HGdCSHGH GdJSYIs - (3GdeNJGQ Hf GdMSf Hf YHOhf Hf HWdGf, GHf HWdGf,J (B444 (3g` s
(3ChdgG (B:s
(3fHJOF HYhf Gddg hfYed LOGhd JJYdb HGdCZPjI hGdCTQHI s
(3BNQgG (B:s
(3hdYd ef jbQC cJGHi gPG jbhd bO YTJ ReGfkG WhjdG de GMJL Edi eG ai gPG GdcJGH ace ef eQI s
(3GdfSNI HgG MhGTs
(3Jdc OGhO Hf eZdWGi GdYajais
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2069) s
Keywords: (3eJaQbGJs